Transformasi Dan Inovasi Di Era Digital Perspektif Pendidikan Kekinian - Ritonga, Mahyudin; Saputra, Riki; Ridwan, Muhammad; Julhadi, Julhadi (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
Information is becoming more widely available in the era of globalization. Conventional paradigms in education have been changed by digital technology, including the internet, mobile devices, and computer-based learning resources. In addition, the development of a competency-based education system forces us to adapt to the demands of the ever-growing labor market. Knowing how Latest Education works: Transformation and Innovation in the Digital Era is the aim of this research. This research uses a library research approach, which involves reading various books or sources and analyzing references and findings from related previous research. This method is useful in obtaining a theoretical basis for the problem being sought. Finding a more thorough discussion of a subject or issue is the goal. This subject has been modified to fit the focus of the article. Literature study is a method qualitative of gathering information by looking at books, articles, notes, and other materials that are relevant to the problem you want to address. A lot of knowledge is said to be gained through the process of studying literature. Later, the writer will utilize this knowledge to complete or integrate the compositiong. Several relevant reference materials and previous research findings were studied in this research using library research techniques. The theoretical basis for the problems studied is also provided by reading various books or sources. Finding a more holistic approach to a subject or problem is the goal. This subject has been adopted as the new topic of this article. To gather information, literature studies look at books, papers, notes, and other publications related to the subject being discussed. The process of studying literature is thought to produce a lot of knowledge. The writer will then utilize this knowledge to complete or incorporate his work.